DEMAND MANAGEMENT AND PRODUCTION CAPACITY IN J.LAUFLUEURS SMEs - Ana; Danielson; Novia, Jessica; Marcella, Kenny; Russiana, Nia; Sisca, Veni (Transpublika Publisher, 2022)
In running a business, especially in the service sector, management and production capacity is one of the keys to success. This is because with both of these things being good, the opportunity for shortages and excess production will be avoided. In this study, MSME J.Laufleurs became the object of research and the objectives to be achieved were knowing the pattern of demand, the reservation system used, and how to manage demand and production capacity. This study utilizes qualitative data analysis methods in the form of interviews and documentation, as well as quantitative data analysis methods, namely graph/table analysis. Through the results of the analysis, researchers know that over the last three years MSME J.Laufleurs has increased by 15% every year. In addition, researchers also found problems in this business, namely the lack of manpower in producing bouquets which can increase demand when there are certain events, the working hours applied are considered insufficient and subcontracts are still unable to cover production capacity. Overall for the last three years, J.Laufleurs' business has been doing well, this is evidenced by the increase in production every year. However, so that in the future the management of demand and production capacity can run better, the researcher would like to recommend that J.Laufleurs can add workers, work overtime hours and subcontract 2 people, 1.2 hours and 12 units, respectively.